Biogeochemical functioning of Lake Alaotra (Madagascar): a reset of aquatic carbon sources along the land–ocean aquatic continuum - V. F. Razanamahandry; A. V. Borges; L. Brosens; C. Morana; T. Razafimbelo; T. Rafolisy; G. Govers; S. Bouillon (Biogeosciences)
Our understanding of the role of tropical lakes in regional carbon budgets remains hampered by a lack of data covering the vast diversity of lake types and settings. Here, we provide a first comprehensive survey of the carbon (C) biogeochemistry of the Lake Alaotra system, a large shallow lake (surface of 200 km2 and maximum depth of 2 m) surrounded by an extensive floodplain and rice fields located in the highlands of Madagascar. The current landscape in the region is grassland-dominated and dotted by major gullies called “lavaka”, which have historically been claimed to lead to high erosion rates and would, thus, also mobilize large amounts of soil C. We investigated the seasonal variability in the concentrations and stable isotope ratios of inorganic and organic C pools; moreover, we examined a range of other relevant proxies, including physicochemical parameters, dissolved CO2 and CH4 concentrations, total alkalinity, and chlorophyll a (Chl a) from spatially distributed sampling and seasonal monitoring of several rivers. While rivers were found to carry high total suspended matter (TSM) loads with a modest particulate organic C (POC) content, the lake itself and its outflow were characterized by much lower TSM values and a high relative contribution of POC to TSM (% POC). The POC concentration of the outflow (13.0±7.7 mg L−1) was substantially higher than in the inflowing water (1.9±2.1 mg L−1), and δ13C values were also distinct between inflowing water (-24.6±1.8<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="eb09ad43f83459b3fb2359015affb213"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2403-2025-ie00001.svg" width="58pt" height="10pt" src="bg-22-2403-2025-ie00001.png"/></svg:svg> ‰) and the lake (-26.5±2.1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="1fd635a4e20b16f9df1ed885ef75505b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2403-2025-ie00002.svg" width="58pt" height="10pt" src="bg-22-2403-2025-ie00002.png"/></svg:svg> ‰) or its outflow (-25.2±1.4<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="330578752b397c30cda3b5d6fc8d1a90"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2403-2025-ie00003.svg" width="58pt" height="10pt" src="bg-22-2403-2025-ie00003.png"/></svg:svg> ‰). Similarly, the lake outflow was surprisingly rich in dissolved organic carbon (DOC) (9.5±1.4 mg L−1) compared to inflowing water (2.6±1.1 mg L−1). This indicates that the lake and its surrounding wetlands act as a substantial source of additional organic C which is exported downstream. The CO2 and CH4 concentrations in inflowing and outflowing rivers were substantially higher than in lake waters, and they peaked during the rainy season due to lateral inputs from wetlands. However, sources of POC and DOC were uncoupled: δ13C data indicated that marsh vegetation was the main source of net DOC inputs, while phytoplankton contributed substantially to POC in the lacustrine waters, at least during parts of the sampling period. Indeed, lake suspended matter has relatively low POC /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="493c42bdafda293669646c99f86fe0ce"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2403-2025-ie00004.svg" width="8pt" height="14pt" src="bg-22-2403-2025-ie00004.png"/></svg:svg> Chl a ratios (143–564, particularly during the May sampling period), high % POC (10 % to 29 %), and δ13C values (-26.5±2.1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="58pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="57bde3908276e42d3d51f626a12d4066"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="bg-22-2403-2025-ie00005.svg" width="58pt" height="10pt" src="bg-22-2403-2025-ie00005.png"/></svg:svg> ‰) distinct from those in marsh-derived organic matter. Despite the evidence for phytoplankton production as a contributor to the lake POC pool, the lake acted as a net source of CO2 to the atmosphere, likely due to the high C inputs from the surrounding marshes and to sediment respiration (considering the shallow water depth). Nevertheless, the partial pressure of CO2 (pCO2) levels in the surface waters of the lake were lower than those in the inflowing and outflowing rivers. This reduction is likely due to the combined effects of phytoplankton production, which assimilates CO2 during photosynthesis, and degassing processes. When CO2-supersaturated riverine water enters the open lake, increased turbulence caused by wind fetch enhances gas exchange with the atmosphere, allowing CO2 to escape more readily from the water column. The biogeochemical functioning of Lake Alaotra differs substantially from the large and deeper East African (sub)tropical lakes and is more similar to lakes surrounded by flooded forests in the Congo River basin, likely due to a combination of its large surface area and shallow water depth and the large extent of surrounding wetlands and floodplains. It acts as an abrupt element in the land–ocean continuum of the catchment, whereby the biogeochemical characteristics of the Maningory River (i.e. the lake outflow) are strongly determined by processes taking place in Lake Alaotra and its wetlands, rather than being reflective of characteristics and processes further upstream in the catchment.